(untitled) (Palíndromo, 2025)
The biography of beauty goes to a long road, which we decided to reconstruct from the point of view of Western historicity and epistemology (theory of knowledge). It was born in the pre-Socratics, with notions that link beauty to (im)permanence. Its most loquacious record appears for the first time in Plato (2021) and, diverging or complementing his master, in Aristotle (2008). Since then, based on the central concept of Logos, we can see that beauty is inextricably linked to the idea of abstraction, purity, divinity. In the Renaissances (Italian and Nordic), beauty shows in a clearer way that oppositions cannot actually survive at its core, as it approached the absolute. The Baroque, resuming medieval powers, reinserts darkness and ugliness to highlight the beautiful (Caetano, 2024b). Romanticism takes up Aristotle and brings him back, based on Kant (1998), taking a “logic of beauty” (Baumgarten, 2007), which, however, needs to be communicated to all people. Whatever it may be, beauty, in its most obvious manifestation, which is art, precedes the need to contextualize the human being in its historical, cultural and anthropological spheres, as demonstrated by the Psychoanalyses of Freud (2011) and Jung (2011a, 2011b).